Quality of life following an open Latarjet-Bristow procedure in a general population with recurrent anterior shoulder instability - Collen S. Nkosi, MBChB (UL); Nyiko Z. Chauke, MBChB(UL), FC Orth(SA), Mmed Ortho Surg (Wits) (JSES International, 2023)
Background: Despite the extensive literature on anterior glenohumeral instability, to date, there are no studies that report on the quality of life following a Latarjet-Bristow procedure with recurrent anterior shoulder instability. The purpose of this study was to evaluate the quality of life in patients who had a Latarjet-Bristow procedure. Methods: A single-center retrospective review with a prospective recall of patients who underwent a Latarjet-Bristow technique for recurrent anterior glenohumeral instability between January 2017 and March 2020. Outcomes measures included health-related quality of life using the Short Form-36 (SF-36) questionnaire and patient-related outcome measures using the Western Ontario Shoulder Instability Index and Rowe scores. Results: A total of 66 patients were identified to participate in the study; 40 (60.6%) responded and were included in the analysis. There were nine females and 31 males, with a median age of 32 years (27.5‒41 years). Three cases had bilateral anterior shoulder instability with a single joint being operated and three patients were epileptic. Physical and mental components summary of the SF-36 showed a better health-related quality of life in the general population. There was a significant strong correlation between SF-36 and Western Ontario Shoulder Instability Index. However, SF-36 and Rowe score showed a fair correlation. Conclusion: The Latarjet-Bristow procedure improves the quality of life in a general population similarly to an athletic population. The number of episodes of dislocation before surgery and the delayed surgical intervention did not increase the recurrent anterior shoulder instability rates postoperatively.